The People's Republic of China : Financial Sector Assessment Program; Systemic Oversight of Financial Market Infrastructures. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2018)
This Technical Note analyzes financial stability issues related to financial market infrastructures (FMIs) in China. Since the previous Financial Sector Assessment Program, the supervision and oversight of FMIs has strengthened through the adoption of the CPSS-IOSCO (Committee on Payment and Settlement Systems/International Organization of Securities Commissions) Principles for FMIs (PFMI). The public adoption of the PFMI by the authorities in 2013 and the establishment of an interagency platform to assess FMIs are commendable. Full implementation of the principles by FMIs is the next step and is expected to enhance the resilience and stability of the FMIs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet